From Asia-Pacific to Indo-Pacific: Significance, implementation and challenges - Felix Heiduk; Gudrun Wacker (Stiftung Wissenschaft und Politik (SWP), 2020)
More and more states and regional organisations employ the term 'Indo-Pacific'. It is increasingly supplanting the previously common term, 'Asia-Pacific'. In Europe, only France has so far presented its own 'Indo-Pacific' concept. The term 'Indo-Pacific' is used to refer to various, sometimes divergent, concepts. These in turn are based on very different ideas on regional order. What they all have in common is the reference to the importance of a rules-based international order. 'Indo-Pacific' is a political term and therefore neither purely descriptive nor value-neutral. In particular, the Trump administration's 'Free and Open Indo-Pacific' concept aims to contain China and is thus an expression of the growing strategic rivalry between Washington and Beijing. In Beijing, 'Indo-Pacific' is primarily understood as a U.S.-led containment strategy directed against China. Other actors, for example ASEAN or India, emphasise aspects such as economic prosperity, connectivity and multilateral cooperation in their Indo-Pacific concepts. The EU and its member states are under increasing pressure from Washington to commit themselves directly or indirectly to the 'Indo-Pacific' - and thus, from a U.S. perspective, for Washington and against Beijing. In their deliberations, Europeans should not succumb to this zero-sum logic. The EU and its member states have at their disposal three (ideal type) approaches: 'equidistance', 'alignment' and 'autonomy'. In order to be able to choose one option, Europeans must define their economic, security and normative interests in the region and provide the necessary resources for their advancement.
Keywords: 320